Efficiency Enhancement in Photovoltaic–Thermoelectric Hybrid Systems through Cooling Strategies - Selcuk Bulat; Erdal Büyükbicakci; Mustafa Erkovan (Energies, 2024)
The integration of photovoltaic (PV) and thermoelectric (TE) modules in PV-TE systems has shown potential for expanding the utilization of the solar spectrum, enhancing the total power output, and reducing the space that is required for PV power plants. This paper discusses the characteristics of a practical PV-TE system model. Typically, to boost the power output of the TE component, a significant temperature difference is induced across the thermoelectric generator (TEG) module using various heat removal methods. These cooling techniques not only enhance the TEG module’s efficiency but may also improve the performance of the PV component. In this study, we evaluate the efficiencies of PV-TE systems that are equipped with polycrystalline silicon solar cells and seven distinct TEGs under four different conditions. Initially, the PV-TE hybrid systems are tested without a cooling mechanism at an ambient temperature of 25 °C (Standard Test Conditions EN/IEC 61215). Subsequently, we examine the systems with a passive cooling approach, employing aluminum heat sinks to facilitate improved heat dissipation. Further tests involve an active cooling system using water and then nanofluid as coolants. The results from these assessments aim to establish a benchmark for enhancing the efficiency of future PV-TE systems.